On the Origin of the Idiom Kogda na gore rak svistnet (When the Crawfish Whistles on the Mountain) - Konickaja, Jelena (Literatūra, 2025)
The article explores the origin of the Russian idiom kogda na gore rak svistnet (meaning: “never; at an indefinite time in the future”) by using methods of diachronic phraseology. Popular existing theories about the expression’s origin do not withstand critical scrutiny. Analysis of Russian language data reveals sporadic appearances of a second component in the idiom – singing fish. A comparative structural-semantic analysis across several languages (Belarusian, Ukrainian, Polish, Slovenian) shows a parallel in Polish with a two-part idiom structure (jak rak świśnie, a ryba piśnie). A similar two-part structure is found in the Slovenian expression iti rakom žvižgat in ribam gost, which carries a different meaning: “to be in vain, unsuccessful; to perish; to die”. Folkloric and mythological evidence from the Balto-Slavic region (Slovenian, Lithuanian, Belarusian, etc.) suggests a rudimentary preservation in the Russian idiom of the so-called ‘primary myth’ – the opposition between the Thunder God (i.e., Perun) and the lord of the underworld (Veles). Structural elements of the idiom (the crawfish as a chthonic creature, whistling as its attribute, and the mountain) support the interpretation of the idiom’s event as situated within a mythological space.
Keywords: Slavic phraseology; diachronic phraseology; kogda na gore rak svistnet; Baltic mythology; Slavic mythology